A nanosheet molding method to estimate the size of bilayers suspended in liquids. Issue 42 (19th October 2022) - Sasaki, Koki; Hernandez Gaitan, Jose A.; Tokuda, Yuki; Miyake, Koji; Uchida, Yoshiaki; Nishiyama, Norikazu
Abstract : We have successfully evaluated the dynamics of bilayers of the hyperswollen lamellar phase by observing palladium nanosheets growing in the bilayers. This method can measure the size of such stimuli-sensitive bilayer structures in situ . Abstract : Various methods have been developed to determine the size of molecular bilayer structures dispersed in liquids. We focused on the nanosheet (NS) growth inside the bilayers in hyperswollen lamellar (HL) phases. Here, we propose the method to evaluate the size of bilayers in liquid by observing palladium NSs (PdNSs) growing rapidly in the bilayers of the HL phase. It uncovered that the width of PdNSs depends on methanol concentration, on which the stability of the HL phase also depends. Considering that the stability of the HL phase is positively correlated with the width of bilayers, we concluded that the observation of PdNSs probably corresponds to the indirect measurement of the width of bilayers. This method will also be applied to various other bilayers. Moreover, the PdNSs of a few nanometers in thickness and several hundred nanometers in width show higher catalytic activity for the reduction reaction of 4-nitrophenol to 4-aminophenol than the previously reported Pd catalysts without any supports.